The Position of Bankruptcy Law and PKPU As a Legal Protection for Concurrent Creditors - Adolf Theodore B. Simanjuntak; Zainal Arifin Hoesein (Cognitionis Civitatis et Politicae, 2024)
The monetary crisis that hit almost all parts of the world in mid-1997 has devastated the joints of the economy. To overcome the problems that arise in the world of businesses that go bankrupt and will result in the fulfillment of obligations that are due, the government made changes in the legislation by revising the existing Bankruptcy Law. The system used in the amendment of the Bankruptcy Law is not to make total changes, but only to change certain articles that need to be changed and add various new provisions to the existing Law. With the development of time in this case, it is necessary to change the Law by improving, adding, and eliminating provisions that are no longer in accordance with the needs and legal developments in society, so the idea arose to change the existing Law into Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations. The result of this research is that in principle, concurrent creditors also have the same position as other creditors on the debtor's bankruptcy assets, both existing and future, after previously deducting debt payment obligations to creditors holding security rights and creditors with special rights holders professionally according to the ratio of the number of receivables of each concurrent creditor.